The Influence of Sharia Financial Literacy on Children's Interest in Saving at Al-Adzan TPA Balikpapan - Achmad Surgawan; Iskandar Yusuf (Al-Fadilah: Islamic Economics Journal, 2024)
Financial literacy education is one of the soft skills that must be taught and instilled in school students from an early age, as well as character education as a provision to prepare children when they become adults to gain financial prosperity. Problems related to financial literacy exist in the Sentul Learning Studio, namely because students often spoiled with pocket money as a substitute for everyday left to work by their parents. However, due to the age factor, children's financial literacy is very minimal, coupled with the lack of financial management education provided in the family. Discipline in financial management is considered as one of the factors that can influence the future life of children, so that the activities carried out are providing teaching of financial management to early childhood through a culture of saving